Aspectos institucionais e legais da transferência internacional de tecnologia na América Latina - Fabíola Pinto Coelho Solha de Carvalho (2017)
The objective of this work is the study of technology transfer in Latin America concerning its legal and institutional aspects, with focus on Argentina, Brazil, Chile, Colombia and Mexico. It analyses, in a brief manner, the main international treaties and conventions regarding intellectual property rights and the main institutions involved in the subject. It presents notions of contract law, its modalities, aspects and clauses that have significant relevance in international legal instruments. It also evaluate the relevant legal provisions of the Constitution of Brazil and the Industrial Property Law (9.279/96) that are related to technology transfer, as well as the main changes contained in the new Code of Science, Technology and Innovation (13.243/16). Finally, it relates the classic models of technology transfer and alternative models that involve transfer and sharing of technology.